Pengaruh Motivasi Belajar Terhadap Hasil Belajar Siswa - Darmawan, Didit; El Barkah, Achmad Afad (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Indragiri (UNISI), 2026)
Teaching morality, ethics, mutual respect, and the priority of the common good over personal interests is the primary goal of educational institutions. This study aims to analyze the influence of learning motivation on the academic performance of middle school students. Motivation to learn is an important factor that influences students' success in achieving optimal learning outcomes. This study is a qualitative investigation that analyzed several relevant scientific sources, including literature, research reports in the form of journals with theories on the subject, and reference materials. The research results show that learning motivation has a positive and significant influence on students' academic achievement. This finding indicates that the higher the students' learning motivation, the better their academic achievement. Therefore, efforts are needed from various parties, particularly teachers and parents, to increase students' learning motivation so that academic achievement can reach an optimal level.